Analisis Kadar Besi (Fe) pada Daun Ubi Kayu (Manihot utilissima) Secara Spektrofotometri Serapan Atom (SSA) - Jamaluddin, Jamaluddin (Media Eksakta, 2011)
A research iron (Fe) concentration analysis has been done on cassava leaf (Manihot utilissima) through Atomic Absorption Spectrophotometry. The aim of the investigation was to determine the iron concentration within the cassava and yellow cassava so as to meet the nutrition fact value especially for preventive of anemia. The samples was separated between cassava leaf and yellow cassava leaf then destructed by dried ashing further analyzed qualitative by chemical reagens and analyzed quantitatively by Atomic Absorption Spectrophotometry at wave length 248,33 nm. From the investigation obtained that the cassava leaf containing iron (Fe) 13,169 mg per 100 gram of the sample and the yellow cassava leaf containing iron (Fe) 14,123 mg per 100 gram of the sample.